Use the Chain Rule to determine an equation for the acceleration when 𝑎 = 𝑑𝑣/ 𝑑𝑡
When 𝑣 = (2𝑡2 + 3)4
and
When 𝑣 = ln(4𝑡3 − 1)
1)When "v = (2t^2+3)^4 = f(g(t))", where "f(t) = t^4, g(t) = 2t^2 + 3" .
Since "\\frac{df}{dt} = 4t^3" and "\\frac{dg}{dt} = 4t" , by the chain rule, we obtain that:
"a = \\frac{dv}{dt} = \\frac{df}{dg} \\frac{dg}{dt} = 4(2t^2+3)^3 \\cdot 4t = 16t(2t^2+3)^3"
2)When "v = ln(4t^3-1) = f(g(t))", where "f(t) =ln( 4t^3-1), g(t) = (4t^3 - 1)" .
Since "\\frac{df}{dt} =\\frac{1}{4t^3-1}" and "\\frac{dg}{dt} =12t^2" , by the chain rule, we obtain that:
"a = \\frac{dv}{dt} = \\frac{df}{dg} \\frac{dg}{dt} = \\frac{1}{4t^3-1}\\cdot 12t^2 = \\frac{12t^2}{4t^3-1}"
Comments
Leave a comment